FORCE LOAD ON MINE TRAWL ASSEMBLIES DURING EXPLOSION - Artym, V. I.; Senchishak, V. M.; Yanitskyi, Yu. B.; Shkitsa, Ya. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
Heavy armoured vehicles used as a mine trawl vehicle are subjected to high loads from the shock wave during demining. The study of mechanisms for reducing the force load on mine trawl components during an explosion is relevant, of scientific and practical value. Therefore, the aim of the work is to reduce the force load on a mine trawl vehicle in the event of an explosion, and to make it possible to use existing motor-tractor equipment of less mass as vehicles for mine trawls. In the actuating mechanism, the mine trawl roller is rigidly connected through a rocker arm to the comb, which, when exploded, enters the ground with spikes, creates a rigid pinching resistance, while reducing the force load on the vehicle. The force load on the comb spike was determined, depending on the mechanical characteristics of the soil, which made it possible to determine the number of spikes to obtain the required load reduction on the mine trawl components. To reduce the maximum peak impact load on the vehicle at the time of explosion, the installation of an elastic shock absorber between the actuator and the vehicle is justified. The obtained results make it possible to reduce the power load on the mine trawl components in order to use existing motor-tractor equipment of lower mass as vehicles.